The influence of neonatal infections on the development of cerebral palsy - Sternal, Marta; Kwiatkowska, Barbara; Borysławski, Krzysztof; Tomaszewska, Agnieszka (Anthropological Review, 2021)
One of the most significant biological factors predisposing to cerebral palsy (CP) are infections. The paper aims to analyze neonatal infections’ influence in the risk of CP development with consideration of all significant risk factors including single, twin, full-term and pre-term pregnancies. 278 children with CP attending the chosen school-educational centers in Poland were included in the questionnaire. The control group included data obtained from the medical documentation of 435 children born in Limanowa County Hospital, Poland. Socio-economic factors, factors connected with pregnancy, and the coexisting disorders and diseases in children were taken into consideration. Constructed models of logistic regression were applied in the statistical analysis. Neonatal infections increase the risk of CP development in all children (odds ratio (OR) 5.1, 95% confidence interval (CI) 2.6–9.8), children from single pregnancies (OR 5.8, 95% CI: 3.0–11.29), full-term (OR 6.2, 95% CI: 3.2–12.3), and single full-term pregnancies (OR 6.0, 95% CI: 3.0–12.0). The influence of neonatal infections in the risk of CP development in children from pre-term and single premature pregnancies was not indicated. Neonatal infections are an independent risk factor for CP development in newborns from full-term pregnancy (>37 weeks of pregnancy). The patho-mechanism of CP is different in children from full-term and premature pregnancy and results from interrelating factors are discussed in this paper.